Representaciones sociales de la inclusión de la población LGBT en educación superior: Representaciones sociales de la inclusión de la población LGBT en educación superior (2020)
LGBT people continue to be victim of discrimination, exclusion, and violence due to the prejudices that circulate about them in society, these being the product of a process of anchoring social representations in which, for centuries, these social sectors were categorized as sinners, criminals, or sick people. This discrimination continues to appear despite the decriminalization and depathologization of sexual diversity in the 20th century and the active presence of people with non-hegemonic gender identities and sexual orientations. From this presence, there were predictions of changes in the current public sphere and in future generations that would favor inclusion of these people. These representations were analyzed in the research Representaciones sociales de la inclusión de la población lgbt en la educación superior, en las facultades de salud de una institución Universitaria de Bogotá D. C., Colombia, carried out in three health sciences faculties, in which many people with sexual orientations and non-hegemonic gender identities feel stereotyped and judged, as evidenced by previous research on stigma and discrimination against LGBT people. Taking into account this background, the purpose of this research was to determine the concepts and beliefs of students, teachers, and administrators in relation to this population, as well as to study the role of sociodemographic characteristics such as gender, age, religion, customs, and educational level in the anchoring of these concepts and beliefs. Among other aspects, it was found that certain religious discourses continue to reproduce prejudices around these groups and are therefore an obstacle to the adequate work of health professionals.